Respuesta :
Answer:
[tex]r=-3[/tex]
Step-by-step explanation:
We have the equation:
[tex]\displaystyle \frac{1}{3}r+1=-\frac{2}{3}r-2[/tex]
And we would like to solve for r.
First, we can multiply both sides by the denominator 3. This will remove the fractions. So:
[tex]\displaystyle 3(\frac{1}{3}r+1)=3(-\frac{2}{3}r-2)[/tex]
Distribute:
[tex]\displaystyle r+3=-2r-6[/tex]
Now, we can add 2r to both sides:
[tex]3r+3=-6[/tex]
And we can also subtract 3 from both sides:
[tex]3r=-9[/tex]
Finally, we can divide both sides by 3 to get:
[tex]r=-3[/tex]